2016
DOI: 10.1371/journal.pone.0161966
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Diabetes and First Evidence for the Utility of HbA1c for Diagnosis and Detection of Diabetes in Urban Black South Africans: The Durban Diabetes Study

Abstract: ObjectiveGlycated haemoglobin (HbA1c) is recommended as an additional tool to glucose-based measures (fasting plasma glucose [FPG] and 2-hour plasma glucose [2PG] during oral glucose tolerance test [OGTT]) for the diagnosis of diabetes; however, its use in sub-Saharan African populations is not established. We assessed prevalence estimates and the diagnosis and detection of diabetes based on OGTT, FPG, and HbA1c in an urban black South African population.Research Design and MethodsWe conducted a population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
73
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 26 publications
3
73
1
1
Order By: Relevance
“…Ethnicity is not considered as an independent risk factor for T2DM in this analysis, although individuals with either a mixed or black African ancestry have a greater risk due to their genetic predisposition. [22][23][24] The predicted T2DM risk of this study population may thus be an underestimation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Ethnicity is not considered as an independent risk factor for T2DM in this analysis, although individuals with either a mixed or black African ancestry have a greater risk due to their genetic predisposition. [22][23][24] The predicted T2DM risk of this study population may thus be an underestimation.…”
Section: Discussionmentioning
confidence: 82%
“…It is, however, well known that individuals with either a mixed or black African ancestry have a greater risk of developing T2DM due to a presumed genetic predisposition. [22][23][24][25] It is thus noteworthy that the predicted T2DM risk of this study population is likely to be an underestimation. Despite this limitation, the current study identified an opportunity for interventional strategies towards T2DM risk reduction by targeting specific modifiable risk factors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…HbA1c measurement is an important tool in the management of patients with DM. Evidence for the utility of HbA1c for the diagnosis and detection of DM in an SA population has been described by Hird et al [12] However, in SA primary healthcare facilities, random blood glucose measurement is commonly used to make clinical decisions with regard to glycaemic control, as HbA1c tests have not been done or the results are not yet available or are out of date. [13] In addition, the DiabCare Africa study found that <50% of patients with DM had had an HbA1c test as part of their management during the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In addition, the DiabCare Africa study found that <50% of patients with DM had had an HbA1c test as part of their management during the previous year. [12] To this end, the availability of a rapid and accurate method of HbA1c evaluation is of paramount importance. [14] According to Gaziano et al, [15] since the late 1990s, deaths due to non-communicable diseases have increased steadily in adults aged ≥50 years.…”
Section: Discussionmentioning
confidence: 99%